Salmonella meningitis and its complications in infants. - Lee, W.S.; Puthucheary, S.D.; Omar, A. (Wiley, 1999)
Infants who developed neurological complications as a result of Salmonella meningitis had significant mortality and adverse long-term neurodevelopment outcome.